2013
DOI: 10.1038/ki.2013.96
|View full text |Cite|
|
Sign up to set email alerts
|

Audit-based education lowers systolic blood pressure in chronic kidney disease: the Quality Improvement in CKD (QICKD) trial results

Abstract: Strict control of systolic blood pressure is known to slow progression of chronic kidney disease (CKD). Here we compared audit-based education (ABE) to guidelines and prompts or usual practice in lowering systolic blood pressure in people with CKD. This 2-year cluster randomized trial included 93 volunteer general practices randomized into three arms with 30 ABE practices, 32 with guidelines and prompts, and 31 usual practices. An intervention effect on the primary outcome, systolic blood pressure, was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 64 publications
(65 reference statements)
0
82
0
Order By: Relevance
“…Similarly, the optimal frequency of BP monitoring is guided more by individual clinical circumstances. Audit-based education is a useful method to support BP monitoring efforts, augment guidelines, and help clinicians achieve systolic BP targets in people with CKD 83. Remote monitoring is an emerging area that may have a role to play among the large population of people with CKD and hypertension 84…”
Section: Managing People With Ckdmentioning
confidence: 99%
“…Similarly, the optimal frequency of BP monitoring is guided more by individual clinical circumstances. Audit-based education is a useful method to support BP monitoring efforts, augment guidelines, and help clinicians achieve systolic BP targets in people with CKD 83. Remote monitoring is an emerging area that may have a role to play among the large population of people with CKD and hypertension 84…”
Section: Managing People With Ckdmentioning
confidence: 99%
“…Data collected for the Quality Improvement in Chronic Kidney Disease (QICKD) trial 35 from 127 primary care practices across England were used to identify and follow-up females with GDM. The trial data comprise routinely collected primary care records between January 2006 and December 2010, from a nationally representative sample of urban, suburban, and rural practices in London, Surrey, Sussex, Leicestershire, the West Midlands, and Cambridgeshire.…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, the largest study to date, QICKD, reported its outcomes [36]. This was a cluster randomized controlled trial of 93 primary care practices examining an audit-based education strategy.…”
Section: Discussionmentioning
confidence: 99%